2022
DOI: 10.3389/fchem.2022.819969
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products and Nanotechnology Against Coronavirus Disease 2019

Abstract: Coronavirus disease 2019 (COVID-19) is a new and severe infectious disease and new global disaster and is spreading rapidly worldwide. Natural products have a long history and have been widely used to treat various acute, chronic, and even life-threatening diseases worldwide. However, the natural products have reduced bioavailability and availability as they have poor kinetic properties, such as large molecular weight, inability to cross lipid membranes, and weak absorption ability. With the rapid development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 87 publications
0
12
0
Order By: Relevance
“…60 Nanotechnology has developed rapidly in recent years and provides an excellent means to overcome the bottleneck of conventional therapies that cause non-specic effects on body tissues, improve the effectiveness of drug and radiation therapy, and greatly reduce adverse effects. [61][62][63] These materials can be used as drug carriers, imaging contrast agents, photothermal materials, photoacoustic compounds and radiation dose enhancers. 64,65 Recently, with the increased understanding of acidic TME, it has been recognized as a new target for tumor diagnosis and treatment, which has important implications for the design of pH-responsive nanomedicines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…60 Nanotechnology has developed rapidly in recent years and provides an excellent means to overcome the bottleneck of conventional therapies that cause non-specic effects on body tissues, improve the effectiveness of drug and radiation therapy, and greatly reduce adverse effects. [61][62][63] These materials can be used as drug carriers, imaging contrast agents, photothermal materials, photoacoustic compounds and radiation dose enhancers. 64,65 Recently, with the increased understanding of acidic TME, it has been recognized as a new target for tumor diagnosis and treatment, which has important implications for the design of pH-responsive nanomedicines.…”
Section: Discussionmentioning
confidence: 99%
“…60 Nanotechnology has developed rapidly in recent years and provides an excellent means to overcome the bottleneck of conventional therapies that cause non-specific effects on body tissues, improve the effectiveness of drug and radiation therapy, and greatly reduce adverse effects. 61–63 These materials can be used as drug carriers, imaging contrast agents, photothermal materials, photoacoustic compounds and radiation dose enhancers. 64,65…”
Section: Discussionmentioning
confidence: 99%
“…Nanotechnology has developed rapidly in recent years, providing a good means to overcome the bottleneck problem of nonspecific and non-selective damage to body tissues caused by traditional therapies (e.g., chemotherapy, radiotherapy and immunotherapy), and exhibiting unique advantages in improving the effects of drugs and radiation therapy while reducing adverse reactions (44,(56)(57)(58). On the one hand, multifunctional nanocarriers can selectively transport therapeutic drugs by utilizing the difference between the tumor tissue and normal tissue to enhance drug permeability and retention.…”
Section: Smart Np-based Systems For Bc Treatment Based On the Tmementioning
confidence: 99%
“…Nanomaterial will be a viable treatment to save more lives since nanomaterial makes it easier to create simple, quick, and low-cost diagnostic assays for SARS-CoV-2 and associated biomarkers ( Zeng et al, 2021 ). Studies have shown that nanomaterial can effectively deliver viral antigens to antigen-presenting cells or serve as adjuvants in the host, so as to produce vaccine rapidly ( Zeng et al, 2022 ). And treatments based on nanomaterials may also decrease SARS-CoV-2 multiplication and reduce inflammation ( Phuna et al, 2022 ).…”
Section: Anti-inflammatory Effects Of Npsmentioning
confidence: 99%